First-line talazoparib plus enzalutamide versus placebo plus enzalutamide in men with metastatic castration-resistant prostate cancer and homologous recombination repair gene alterations: patient-reported outcomes from the randomised, double-blind, placebo-controlled, phase 3 TALAPRO-2 trial - Fay, André; Fizazi, Karim; Matsubara, Nobuaki; Azad, Arun A; Saad, Fred; De Giorgi, Ugo; Joung, Jae Young; Fong, Peter C C; Jones, Robert J; Zschäbitz, Stefanie; Oldenburg, Jan; Shore, Neal D; et al. (The lancet. Oncology, 2025)
Background - In the phase 3 TALAPRO-2 trial, talazoparib plus enzalutamide significantly improved radiographic progression-free survival compared with placebo plus enzalutamide in men with metastatic castration-resistant prostate cancer harbouring alterations in genes involved in homologous recombination repair (HRR). We aimed to assess patient-reported outcomes in patients with HRR-deficient metastatic castration-resistant prostate cancer in TALAPRO-2. - Methods - TALAPRO-2 is a randomised, double-blind, placebo-controlled, phase 3 trial conducted at 223 hospitals, cancer centres, and medical centres in 26 countries worldwide. Eligible participants were male patients aged 18 years or older (≥20 years in Japan) who were receiving ongoing androgen deprivation therapy, had asymptomatic or mildly symptomatic metastatic castration-resistant prostate cancer, an Eastern Cooperative Oncology Group performance status of 0 or 1, and had not received previous life-prolonging systemic therapy for castration-resistant prostate cancer or metastatic castration-resistant prostate cancer. Patients with HRR gene alterations were randomly assigned (1:1) using a centralised interactive web response system and a permuted block size of 4 to oral talazoparib 0·5 mg once daily or placebo, plus oral enzalutamide 160 mg once daily, stratified by previous second-generation androgen receptor pathway inhibitor (abiraterone or orteronel) or docetaxel (yes vs no) in the castration-sensitive setting. The sponsor, patients, and investigators were masked to allocation of talazoparib or placebo; enzalutamide was open-label. The primary endpoint was radiographic progression-free survival by blinded independent central review and has been reported previously. Patient-reported outcomes were assessed as secondary outcomes in the patient-reported outcomes population, which comprised patients from the intention-to-treat population with a baseline patient-reported outcome assessment and at least one post-baseline patient-reported outcome assessment. Patient-reported outcomes included time to definitive deterioration in global health status/quality of life (GHS/QoL) per European Organisation for Research and Treatment of Cancer (EORTC) Core Quality of Life Questionnaire (QLQ-C30) and prostate cancer-specific urinary symptoms per EORTC Quality of Life Questionnaire-Prostate (QLQ-PR25), and time to deterioration in pain symptoms per Brief Pain Inventory-Short Form (BPI-SF). Mean change from baseline in GHS/QoL, overall cancer and prostate cancer-specific functioning and symptoms (per EORTC QLQ-C30 and QLQ-PR25), in pain symptoms per BPI-SF, and in general health status per EQ-5D-5L were also patient-reported secondary outcomes. This study is registered with ClinicalTrials.gov, NCT03395197, and is ongoing. - Findings - Between Dec 18, 2018, and Jan 20, 2022, 399 patients with HRR-deficient metastatic castration-resistant prostate cancer were enrolled and randomly assigned, of whom 197 assigned to talazoparib plus enzalutamide and 197 assigned to placebo plus enzalutamide were included in the patient-reported outcome population. Median follow-up was 22·2 months (IQR 13·8-27·7) in the talazoparib plus enzalutamide group and 20·2 months (13·5-26·6) for the placebo plus enzalutamide group. Median time to definitive deterioration of GHS/QoL was longer in the talazoparib plus enzalutamide group (27·1 months [95% CI 21·2-non-estimable]) than in the placebo plus enzalutamide group (19·3 months [16·6-23·0]; hazard ratio [HR] 0·69 [95% CI 0·49-0·97]; two-sided p=0·032). Median time to definitive deterioration in urinary symptoms was also longer in the talazoparib plus enzalutamide group (non-estimable [95% CI 32·2-non-estimable]) than in the placebo plus enzalutamide group (30·2 months [24·6-non-estimable; HR 0·56 [0·34-0·93]; two-sided p=0·022). Median time to deterioration in pain symptoms was non-estimable for both treatment groups (HR 0·58 [0·33-1·01]; two-sided p=0·051). Changes from baseline in worst pain in the past 24 h (BPI-SF, question three) and in general health status (EQ-5D-5L) also favoured talazoparib plus enzalutamide versus placebo plus enzalutamide, although the differences were not clinically meaningful. Between-group differences in mean changes from baseline in GHS/QoL, functioning, and symptoms per EORTC QLQ-C30 did not reach the clinically meaningful threshold of 10 or more points, although physical, emotional, and cognitive functioning and pain favoured talazoparib plus enzalutamide. Similarly, differences in mean changes from baseline for urinary and bowel symptoms per EORTC QLQ-PR25 favoured talazoparib plus enzalutamide, but were not clinically meaningful. - Interpretation - The demonstrated delays in definitive deterioration in GHS/QoL, urinary symptoms, and other functioning and symptom scales with talazoparib plus enzalutamide compared with placebo plus enzalutamide in patients with HRR-deficient metastatic castration-resistant prostate cancer provide insight that might inform clinical decisions for these patients. - Funding - Pfizer.